THE EFFECT OF DEBT TO TOTAL ASSET RATIO AND DEBT TO EQUITY RATIO ON PROFITABILITY IN PLANTATION SUB-SECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE (2016-2018 PERIOD) - Hanifah Ikmala Rizal; Kasmadi Kasmadi; Helmiati Helmiati (Jurnal Riset Manajemen Indonesia, 2021)
This research was conducted with the aim of examining the effect of Debt to Assets Ratio and Debt to Equity Ratio on profitability in plantation sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2018. The population of this research were 12 plantation sub-sector companies listed on the Indonesian stock exchange for the 2016-2018 period. The technique used in sampling is the file research method, all companies are samples in this research. Hypothesis testing uses multiple linear regression analysis. The results showed that simultaneously the Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) had an effect on Return on Assets (ROA). Partially, Debt to Assets Ratio (DAR) has an effect on Return on Assets (ROA), and Debt to Equity Ratio (DER) has no effect on Return on Assets (ROA).